Določanje koncentracije atomarnega kisika s titracijo - Vesel, Alenka (Vakuumist, 2000)
Determination of the O-atom density by the NO titration method is described. The method is based on the introduction of NO into the oxygen discharge. Oxygen atoms react with NO to produce metastable NOsub2*. From the intensity variation of emission spectrum of NOsub2* versus NO the concentration of O-atom density can be deduced. At our experiments the O-atom density was measured by the NO titration method in Ar-Osub2 microwave post-discharge. Plasma was generated with the surfatron MW generator with the frequency of 2.45 GHz and the output power of 60 W. The measurements show that the density of oxygen atoms in Ar-Osub2 discharge at the argon flow of 0.6 l/min (1.3 mbar) and 0.4 l/min (1 mbar) was in the range between 10sup20and 10sup21 msup-3.
Keywords: plazma; kisik; atomi; titracija; dušikov oksid